Functional Limitations Mediate the Relationship Between Pain and Depressive Symptoms in Former NFL Athletes. Issue 5 (October 2019) - Turner, Robert W.; Sonnega, Amanda; Cupery, Tim; Chodosh, Joshua; Whitfield, Keith E.; Weir, David; Jackson, James S.
The objective of this study was to analyze data from the National Football League Player Care Foundation Study of Retired NFL Players to understand potential risks for depressive symptoms in former athletes by investigating the relationship between pain and depressive symptoms in a multivariate context, while simultaneously exploring the potential connection with functional limitations. Descriptive statistics were used to describe the study sample and to conduct bivariate comparisons by race and age cohort. Linear regression models were conducted in the subsample of respondents reporting on depressive symptoms using the PHQ-9. Models examine the relationship of bodily pain, injury as a reason for retirement or not re-signing with a team, length of NFL career, sociodemographic characteristics, chronic conditions, and functional limitations to depression. Interaction terms tested whether race and age moderated the effect of bodily pain and functional limitations on depressive symptoms. Bivariate associations revealed no significant differences between younger and older former players in indicators of pain and only slightly higher functional limitations among younger former players. In the multivariate models, pain was significantly associated with depressive symptoms (β = 0.36; p < .01), net of a range of relevant controls. Adding an index of functional limitations reduced this association by nearly half (β = 0.20; p < .01) and functional limitations was significantly associated with depressive symptoms (β = 0.40; p < .01). No statistically significant interactions were found. Overall, bodily pain was strongly associated with depressive symptoms. After accounting for the effects of functional limitations, this association was notably reduced. These results may be useful in identifying aging-related physical declines in relatively younger adult men who may be at the greatest risk for depression. They highlight how physical functionality and activity may mitigate the risk of depression, even in the presence of significant bodily pain.